Gut Microbiome Toxicity: Connecting the Environment and Gut Microbiome-Associated Diseases - Pengcheng Tu; Liang Chi; Wanda Bodnar; Zhenfa Zhang; Bei Gao; Xiaoming Bian; Jill Stewart; Rebecca Fry; Kun Lu (Toxics, 2020)
The human gut microbiome can be easily disturbed upon exposure to a range of toxic environmental agents. Environmentally induced perturbation in the gut microbiome is strongly associated with human disease risk. Functional gut microbiome alterations that may adversely influence human health is an increasingly appreciated mechanism by which environmental chemicals exert their toxic effects. In this review, we define the functional damage driven by environmental exposure in the gut microbiome as gut microbiome toxicity. The establishment of gut microbiome toxicity links the toxic effects of various environmental agents and microbiota-associated diseases, calling for more comprehensive toxicity evaluation with extended consideration of gut microbiome toxicity.